Development of Paramyosin as a Vaccine Candidate for Schistosomiasis - Jiz, Mario A.; Wu, Haiwei; Olveda, Remigio; Jarilla, Blanca; Kurtis, Jonathan D. (Frontiers in Immunology, 2015)
Abstract: Schistosomiasis, caused by three principal species of dioecious trematodes (flatworms), currently afflicts over 250 million individuals, results in an estimated 2-15% chronic disability, and contributes to poor health and economic stagnation in endemic areas. Although schistosomiasis is effectively treated with praziquantel, rapid reinfection with rebound morbidity precludes effective control based on chemotherapy alone and justifies current efforts to develop vaccines for these parasites. Paramyosin (Pmy), an invertebrate muscle-associated protein, has emerged as a promising vaccine candidate for both Schistosoma mansoni and S. japonicum. Herein, we discuss the discovery of Pmy, its development as a vaccine candidate in rodents and bovines, as well as studies of naturally occurring immune responses to Pmy in prospective, observational human studies. We conclude with a proposed developmental plan to move Pmy toward Phase I clinical trials.